PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA PADA KELAS INKLUSIF DI KABUPATEN JOMBANG BESERTA SOLUSINYA - Yulianah Prihatin; Indah Mei Diastuti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This research aims to find out the problems contained in learning Indonesian at inclusive schools in Jombang and the solution to overcome it. Besides, it is expected to know the weakness of learning Indonesian so that the researcher can design learning program accordance the curriculum used. The result of research shown that: 1) some problems faced in learning Indonesian is the lack of understanding of inclusive students on teacher explanations, lack of facilities and infrastructure, lack of teachers assistant or tutor, lack use of varied learning resources 2) solutions to overcome the problems that occur are: move inclusive students to a quieter class to perform intensive guidance and then returned in the regular class if the students have already understood the explanation given by teachers, need for attention from the government to fulfill the infrastructure facilities of each inclusive education school, fulfill the needs of incisive tutors, form a special group through social media consist of parents of inclusive students and the school to discuss the development of students both school and home, , conduct training for teachers to utilize learning resources to be more varied and utilize technological sophistication to support the utilization of learning resources. Key word: problematic, inclusive class.